Step 1: Combine like terms to get: -z - 12 = -3z + 6
Step 2: Get the x-terms on the same side of the equation: -z + 3z = 6 + 12
Step 3: Get the constants on the same side of the equation: 2z = 18
Step 4: Use Division Property of Equality: z = 9
Fill in the blanks to follow the steps in solving the equation: 5z-12-6z=-10z + 7-1 %0D%0A5%0D%0A%0D%0A−%0D%0A12%0D%0A−%0D%0A6%0D%0A%0D%0A=%0D%0A−%0D%0A10%0D%0A%0D%0A+%0D%0A7%0D%0A−%0D%0A1%0D%0A%0D%0AStep 1: Combine like terms to get: Response area%0D%0A%0D%0AStep 2: Get the x-terms on the same side of the equation: Response area%0D%0A%0D%0AStep 3: Get the constants on the same side of the equation: Response area%0D%0A%0D%0AStep 4: Use Division Property of Equality: Response area
1 answer